Synthesis and antitumor activities of new N-(5-benzylthiazol-2-yl)-2-(heteryl-5-ylsulfanyl)-acetamides - Ostapiuk, Yu.V.; Frolov, D.A.; Vasylyschyn, R.Ya.; Matiychuk, V.S. (Вiopolymers and Cell, 2018)
Aim. Synthesis of series of new N-(5-benzyl-thiazol-2-yl)-2-(heteryl-5-ylsulfanyl)-acetamides and study on their anticancer activity. Methods. Organic synthesis, analytical and spectral meth-ods, pharmacological screening. Results. [2-chloro-N-(5-aryl-1,3-thiazol-2-yl)acetamides 3a-h have been prepared in good yields] by the reaction of 2-amino-5-(R-benzyl)thiazoles with chloroacetyl chloride. The obtained compounds react with 1-phenyl-1H-tetrazole-5- 4, 4-allyl-5-phenyl-4H-[1,2,4]triazole-3- 5a, 4-allyl-5-furan-2-yl-4H-[1,2,4]triazole-3- 5b thioles, pyrimidine-2- 6a and 4,6-dimethyl-pyrimidine-2- thioles 6b to form series of novel N-(5-benzyl-thiazol-2-yl)-2-(heterylsulfanyl)acetamides with yields 65-96%. These compounds have been evaluated for their anticancer activity against 60 cancer cell lines in the concentration of 10 µM. The human tumour cell lines were derived from nine different cancer types: leukemia, melanoma, lung, colon, CNS, ovarian, renal, prostate, and breast cancers. The synthesized compounds displayed moder-ate activity in the in vitro screening with the tested cell lines. However, it was observed a selective influence of some compounds on several cancer cell lines. Compounds 7c, 8a, 8d and 9c-g have been found to be active and highly selective towards the] HOP-92 Non-Small Cell Lung Cancer cell line (GP = 39.45 – 65.63%), whereas 2-(4,6-R1-pyrimidin-2-ylsulfanyl)-N-[(5-R-benzyl)-thiazol-2-yl]-acetamides 9c-h are active towards the UO-31 Renal Cancer cell line (GP = 34.43 – 60.58%). Compounds 7c possessed significant activity towards the SNB-75 CNS Cancer cell line (GP = -3.83 %), 7f – on the OVCAR-4 Ovarian Cancer cell line (GP = 14.66 %), 8d – on the HS 578T Breast Cancer cell line (GP = 11.09%), 9g – on the NCI-H226 Non-Small Cell Lung Can-cer (GP = 9.75%) and UO-31 Renal Cancer cell lines (GP = 16.35%). Conclusions. A series of new 2-amino-5-arylmetylthiazole derivatives was synthesized. It was established that these com-pounds are promising in the search for innovative anti-cancer agents.